Moisture sorption characteristics and quality changes during storage in defatted soy incorporated maize-millet based extruded product. (November 2020) - Sahu, Chandrahas; Patel, Shadanan
Abstract: Moisture sorption isotherms and changes in quality of extruded products during storage were carried out in this experiment. Sorption of extruded product was investigated at four different temperatures 30, 40, 50 and 60 °C using static method. The optimized composite blend of maize: finger millet: defatted soy: elephant foot yam in the ratio of 40:30:20:10 was used to develop extruded product by using twin screw extruder at feed moisture 14% (wb), barrel temperature 110 °C and screw speed 301 rpm. The sorption isotherms were found to be Type II curves for all the experimental temperatures. The data was analyzed by sorption models of GAB, Smith, BET, Caurie, Oswin and Iglesias and Chirife. Regression analysis was performed to find the model constants. Goodness of fit was determined by statistical parameters R 2, %RMSE and %P. GAB model was found to be best fitted. The storage study of extrudates packed in LDPE, HDPE, Al foil and MPET were done at accelerated condition (40 °C and 90% RH). Product moisture, hardness and crispness of the products were found to be varied significantly at 5% level with storage period. MPET was found to be best packaging material for extruded products with longer storage life. Highlights: Sorption study finds the capacity of moisture acceptability of extruded products from the atmosphere. It gives the prediction of shelf-life of the product. Selection of packaging material is important for shelf-life of the product. Storage study plays very crucial role for acceptability of the product.